Development of the ABXGUIDE: a pathogen-directed consensus guideline for antimicrobial use in resource-constrained settings - Hind Kadri; Neda Milevska Kostova; Teske Schoffelen; Souha Kanj; Heiman Wertheim (Journal of Global Antimicrobial Resistance)
AIM: User-friendly up-to-date guidance for antimicrobial therapy in resource-constrained settings is lacking. We aim to address the gap by describing the development process of the ABXGUIDE, which includes online pathogen-directed antibiotic guidelines taking into consideration low-resource settings. BACKGROUND: The threat of antimicrobial resistance (AMR) is particularly pressing in low-and-middle-income countries (LMICs). This is due to the high burden of infectious diseases, limited resources, lacking antimicrobial stewardship (AMS) infrastructure, and limited guidance intended for these conditions. A global stakeholder survey conducted in 2022 confirmed the need for contextualized guidelines on preferred and alternative therapies in resource-constrained settings. The ABXGUIDE provides pathogen-directed antibiotic guidance for multiple bacterial infections, while considering multiple restrictive factors in low-resource settings. METHODS: ABXGUIDE development started by a literature review, compiling five or more guidelines for each infection in adults. Then antibiotic choices for different pathogens were tailored to resource-constrained settings by availability, cost, susceptibility, mode of administration, side effects, and allergies. Tabulated data, which was aligned with the WHO AWaRe classification (2021), was internally reviewed by consensus of four experts, followed by a peer review by two independent experts. RESULTS: The ABXGUIDE online platform exhibits pathogen-directed guidelines on primary therapy and alternative therapies that are suitable for LMICs. Multiple infections are included: respiratory, bloodstream, neurological, urinary, abdominal, skin and cardiac infections. ABXGUIDE offers suggestions on duration of therapy, allergies and side effects, bearing in mind limitations in resource-constrained settings. CONCLUSIONS: ABXGUIDE provides easy access to high-quality pathogen-directed treatment guidelines for multiple bacterial infections optimized for resource-constrained settings.